A method for preparing silicon dioxide composite thermal insulation aerogel

By using materials such as chitosan, sodium lauryl glutamate and quaternary chitosan in silica aerogels, combined with crosslinking agent and air template technology, a silica composite thermal insulation aerogel with high skeleton strength, excellent adsorption ability and thermal insulation properties is prepared, which solves the shortcomings of the existing aerogels in adsorption ability and thermal insulation properties.

CN119143140BActive Publication Date: 2025-03-25NANJING DAMAONIU ENVIRONMENTAL PROTECTION TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411286272.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-03-25
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

The existing silica aerogels have severe shrinkage, low skeleton strength and small pores during production, resulting in insufficient adsorption capacity and lack of thermal insulation and flame resistance.

Method used

By selecting chitosan and silica as the main raw materials, using phthalaldehyde as the crosslinking agent, combining sodium lauroyl glutamate as the air template, and after chitosan is quaternized and modified, it is compounded with hydrophobic silica aerogel powder to prepare a silica composite thermal insulation aerogel with high skeleton strength, excellent adsorption ability and thermal insulation properties.

Benefits of technology

The framework strength and adsorption capacity of silica composite aerogel are improved, their insulation properties are enhanced, and the flame retardant ability is improved, solving the thermal conductivity and porosity problems of the original aerogel in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143140B_ABST
    Figure CN119143140B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a silica composite thermal insulation aerogel. The invention uses o-phthalaldehyde as a cross-linking agent to prepare a silica composite thermal insulation aerogel having a thermal insulation function, high skeleton strength and good adsorption capacity. On this basis, sodium lauroyl glutamate is used as an air template to prepare a new silica composite thermal insulation aerogel. Under the premise of not destroying the overall gel process, the porosity of the aerogel is increased, the separation effect in oil-water separation is further improved, and excellent flame retardancy is shown. Finally, chitosan is selected to be quaternized and modified and then directly compounded with hydrophobized silica aerogel powder to obtain an improved silica composite thermal insulation aerogel, which not only has a more complex and elongated skeleton structure, but also increases the surface area and surface roughness of the gel as a whole, so that its adsorption capacity is further enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention specifically relates to a method for preparing a silicon dioxide composite thermal insulation aerogel. Background Art

[0002] Silica aerogel has been widely studied and actively expanded for its unique porous structure, light weight, low thermal conductivity, high specific surface area and other characteristics. However, it has low strength and is fragile, and it is difficult to perfectly demonstrate its excellent characteristics in practical applications. Therefore, selecting different composite materials and using different gel methods to prepare silica composite aerogels are the current research focuses on the application of silica aerogels.

[0003] Current silica aerogels usually suffer from severe shrinkage during production, have low skeleton strength, and have a small number of pores, resulting in insufficient adsorption capacity. At the same time, they also do not have thermal insulation and flame retardancy functions, and further improvement is needed.

[0004] Therefore, it is necessary to invent a method for preparing a silica composite thermal insulation aerogel to solve the above problems. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a silica composite thermal insulation aerogel. Chitosan and silica are selected as the main raw materials of the composite aerogel, and o-phthalaldehyde is used as a cross-linking agent to prepare a silica composite thermal insulation aerogel with thermal insulation function, high skeleton strength and good adsorption capacity. On this basis, sodium lauroyl glutamate is used as an air template to prepare a new silica composite thermal insulation aerogel. Under the premise of not destroying the overall gel process, the porosity of the aerogel is increased, the separation effect in oil-water separation is further improved, and excellent flame retardancy is shown. Finally, chitosan is selected to be quaternized and modified and then directly composited with hydrophobic silica aerogel powder to obtain an improved silica composite thermal insulation aerogel, which not only has a more complex and elongated skeleton structure, but also increases the surface area and surface roughness of the entire gel, so that its adsorption capacity is further enhanced to solve the above-mentioned shortcomings in the technology.

[0006] In order to achieve the above object, the present invention provides the following technical solution: a silicon dioxide composite thermal insulation aerogel, the raw materials for making the aerogel include, by weight:

[0007] 0.36-0.98 parts of chitosan, 0.746-0.776 parts of acetic acid, 0.885 parts of methyltrimethoxysilane, 0.295 parts of tetraethoxysilane, 3.267 parts of ethanol, 0.916 parts of o-phthalaldehyde, 0.5 parts of silicic acid, and the rest is water.

[0008] The aforementioned silicon dioxide composite heat-insulating aerogel is made from raw materials that further include, by weight: 0.4 parts of sodium lauroyl glutamate and 0.5-3 parts of phytic acid.

[0009] The aforementioned silicon dioxide composite thermal insulation aerogel is made from raw materials that further include, by weight: 3-5 parts of ammonia water, 5-20 parts of n-hexane, and 1-3 parts of trimethylchlorosilane.

[0010] A method for preparing a silicon dioxide composite thermal insulation aerogel comprises the following steps:

[0011] 1.1. Mix 0.39-0.98 parts of chitosan and 0.746-0.776 parts of acetic acid, and stir to dissolve to obtain a chitosan solution;

[0012] The volume percentage concentration of the acetic acid solution was set to 3% v / v, the stirring time was 5 h, the stirring temperature was 50° C., and after stirring and dissolving, four chitosan solutions with different weight percentage concentrations were obtained, specifically: 1.5wt% chitosan solution, 2wt% chitosan solution, 3wt% chitosan solution, and 4wt% chitosan solution;

[0013] 1.2. Add 0.885 parts of methyltrimethoxysilane, 0.295 parts of tetraethoxysilane and 3.267 parts of ethanol to 0.422 parts of water, stir and mix, and let stand to obtain silica sol;

[0014] The stirring time is 1 hour, the stirring temperature is 23°C, and the pH value is adjusted during stirring to a pH value of 2-3, and the standing time is 24 hours;

[0015] 1.3. Mix 0.916 parts of o-phthalaldehyde powder with 5.237 parts of water, and stir to dissolve to obtain an o-phthalaldehyde solution;

[0016] Among them, the stirring time is 10h and the stirring temperature is 65℃;

[0017] 1.4. Mix 25 parts of chitosan solution with 6 parts of o-phthalaldehyde solution. After the first stirring, add 0.5 parts of silicic acid and 5 parts of silica sol for a second stirring. Then transfer the stirred solution to a polypropylene mold and freeze it to prepare a cryogel.

[0018] Wherein, the chitosan solution has a weight percentage concentration of any one of 1.5wt%, 2wt%, 3wt%, and 4wt%;

[0019] Among them, the first stirring time is 3 minutes, the second stirring time is 5 minutes, the freezing temperature is -48°C, and the freezing time is 24 hours;

[0020] 1.5. Transfer the frozen gel to a freeze dryer for vacuum freeze drying to obtain a silica composite thermal insulation aerogel;

[0021] Among them, the drying temperature is -48°C and the drying time is 48h.

[0022] A method for preparing a silicon dioxide composite thermal insulation aerogel comprises the following steps:

[0023] 2.1. Mix 0.36-0.98 parts of chitosan and 0.746-0.776 parts of acetic acid, and stir to dissolve to obtain a chitosan solution;

[0024] The volume percentage concentration of the acetic acid solution was set to 3% v / v, the stirring time was 5 h, the stirring temperature was 50° C., and after stirring and dissolving, four chitosan solutions with different weight percentage concentrations were obtained, specifically: 1.5wt% chitosan solution, 2wt% chitosan solution, 3wt% chitosan solution, and 4wt% chitosan solution;

[0025] The stirring time is 1 hour, the stirring temperature is 23°C, and the pH value is adjusted during stirring to a pH value of 2-3, and the standing time is 24 hours;

[0026] 2.2, 0.916 parts of o-phthalaldehyde powder was mixed with 5.237 parts of water, and the mixture was stirred to dissolve to obtain an o-phthalaldehyde solution;

[0027] Among them, the stirring time is 10h and the stirring temperature is 65℃;

[0028] 2.3, 25 parts of chitosan solution and 6 parts of o-phthalaldehyde solution were mixed, and after the first stirring, 0.5 parts of silicic acid, 0.4 parts of sodium lauroyl glutamate, and 0.5-3 parts of phytic acid were added, and stirred for a second time, and then the stirred solution was transferred to a polypropylene mold and frozen to prepare a cryogel;

[0029] Wherein, the chitosan solution has a weight percentage concentration of any one of 1.5wt%, 2wt%, 3wt%, and 4wt%;

[0030] Among them, the first stirring time is 3 minutes, the second stirring time is 5 minutes, the freezing temperature is -48°C, and the freezing time is 24 hours;

[0031] Among them, phytic acid can be replaced by melamine or aluminum hydroxide;

[0032] 2.4. Transfer the frozen gel to a freeze dryer for vacuum freeze drying to obtain a silica composite thermal insulation aerogel;

[0033] Among them, the drying temperature is -48°C and the drying time is 48h.

[0034] A method for preparing a silicon dioxide composite thermal insulation aerogel comprises the following steps:

[0035] 3.1. Add 0.885 parts of methyltrimethoxysilane, 0.295 parts of tetraethoxysilane and 3.267 parts of ethanol to 0.422 parts of water, stir and mix, let stand to obtain silica sol, and age, ball-mill and dry the sol to obtain aerogel powder;

[0036] The stirring time is 1 hour, the stirring temperature is 23°C, and the pH value is adjusted during stirring to a pH value of 2-3, and the standing time is 24 hours;

[0037] 3.2. Add 0.36-0.98 parts of chitosan to 10-30 parts of isopropanol, then slowly drop glycidyl trimethylammonium chloride, stir, heat, precipitate, soak, rinse and dry to obtain quaternized chitosan;

[0038] 3.3, 3.3-5.5 parts of quaternized chitosan and 1.1 parts of chitosan are mixed and dissolved in 0.746-0.776 parts of acetic acid, and stirring is continued to obtain a quaternized chitosan solution;

[0039] The acetic acid was set to 100 ml of 4 wt% glacial acetic acid solution, the stirring time was 8 h, and the stirring temperature was 50°C;

[0040] 3.4. Add 0.1-0.5 parts of silica aerogel powder into the quaternary ammonium chitosan solution, mix and stir, transfer to a polypropylene mold for freezing, and after freezing, transfer to a freeze dryer for drying to obtain a silica composite thermal insulation aerogel;

[0041] The stirring time was 12 h, and ultrasonic treatment was performed for 30 min after the stirring was completed.

[0042] The aforementioned method for preparing the silica composite thermal insulation aerogel comprises, in step 3.1:

[0043] Among them, one period is half of the entire ball milling treatment time;

[0044] The drying process is specifically as follows: drying the dispersion in a vacuum drying oven to obtain silica aerogel powder;

[0045] The dispersion was dried in a vacuum drying oven at 55° C., 90° C., 115° C. and 0.08-0.09 MPa for 4 hours to obtain silica aerogel powder.

[0046] The aforementioned method for preparing the silica composite thermal insulation aerogel, in step 3.2:

[0047] The stirring process is specifically as follows: the stirring time is 1 hour, the stirring temperature is 40° C., and in the process of maintaining the stirring, glycidyl trimethyl ammonium chloride is added dropwise to the mixture of chitosan powder and isopropanol;

[0048] The specific heating process is as follows: a mixture of chitosan powder, isopropanol and glycidyl trimethylammonium chloride is heated to 80°C in a flask and maintained for 3 hours to obtain a mixed solution.

[0049] The precipitation, soaking and rinsing process is specifically as follows: the mixed solution is transferred into acetone to form a precipitate, the precipitate is removed and then repeatedly soaked and rinsed with ethanol to obtain an unreacted white insoluble substance;

[0050] The drying process is specifically as follows: after the white insoluble matter is dried in a forced air drying oven for 36 hours, the quaternized chitosan can be obtained.

[0051] Compared with the prior art, the present invention has the following beneficial effects:

[0052] 1. A silica composite thermal insulation aerogel was prepared by a cross-linking method. As the concentration of chitosan increased, the complexity of the chitosan network increased, providing more attachment sites for silica particles, so that the density of the silica composite thermal insulation aerogel increased to a certain extent, and the volume shrinkage decreased. Correspondingly, the particle density of silica increased, and the average pore size decreased. The water contact angle of the silica composite thermal insulation aerogel increased, and the thermal conductivity decreased accordingly, showing a large amount of chitosan network structure and a small amount of silica aerogel particle structure. The two together played a supporting role, so that the skeleton strength of the prepared silica composite thermal insulation aerogel was relatively high.

[0053] At the same time, in terms of thermal weight loss, the chitosan component in the system reached more than 48%, which shows that in the early stage of gelation, the chitosan molecular chain was shrunk and entangled by the anti-solvent ethanol, and wrapped a certain amount of silica solution to form an insoluble gel. The stability of the system was destroyed by the chitosan gel, causing the self-assembly gel behavior of the entire system, so that the silica composite thermal insulation aerogel has extremely excellent porosity, that is, it can still maintain the characteristics of low thermal conductivity and high porosity in a high temperature environment, which can expand its operating temperature range, enhance energy-saving effects, and has excellent hydrophobicity and adsorption properties. The thermal insulation performance is also guaranteed;

[0054] 2. A new silica composite thermal insulation aerogel is prepared by using o-phthalaldehyde as a cross-linking agent and sodium lauroyl glutamate as an air template. A large number of bubbles generated by sodium lauroyl glutamate under mechanical stirring are used to form an air template. Flame retardant components can be directly mixed into the silica composite thermal insulation aerogel to improve the performance without affecting the gel reaction. The prepared silica composite thermal insulation aerogel exhibits excellent anti-shrinkage performance after o-phthalaldehyde cross-linking, and the overall shrinkage rate is maintained below 8%. At the same time, after adding sodium lauroyl glutamate, the prepared silica composite thermal insulation aerogel has an increased number of irregular pores, a reduced density, a decreased compression strength, and improved oil absorption performance. When the flame retardant component is introduced during the foaming process, the silica composite thermal insulation aerogel changes from violent combustion to natural extinguishing. The system exhibits good compatibility, thereby improving the flame retardant ability of the silica composite thermal insulation aerogel without destroying the entire gel system.

[0055] 3. Further, quaternized chitosan and silica aerogel powder are used to prepare quaternized silica composite thermal insulation aerogel in an incompatible system. The silica composite thermal insulation aerogel presents a layered sheet structure as a whole. On the sheet surface, the silica and chitosan components are tightly combined. The silica particles retain the pore structure while giving the silica composite thermal insulation aerogel a certain support, so that the silica composite thermal insulation aerogel has a higher skeleton strength;

[0056] At the same time, the thermal weight loss process of the silica composite thermal insulation aerogel shows that the composite of ammonium chitosan and silica aerogel powder does not affect the high temperature resistance of the finished silica composite thermal insulation aerogel.

[0057] In addition, although a small amount of hydrophobic silica powder changes the structure of the finished silica composite thermal insulation aerogel, it does not significantly affect the water contact angle of the gel. The silica composite thermal insulation aerogel shows better adsorption performance in the dye adsorption test. The adsorption ratio of the three anionic dyes reaches about 95%, and the adsorption capacity is further enhanced. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can also be obtained based on these drawings.

[0059] Figure 1 This is a flow chart of the silica composite thermal insulation aerogel prepared in Example 1 of the present invention;

[0060] Figure 2 The appearance and shrinkage rate of the silicon dioxide composite thermal insulation aerogel prepared in Example 1 of the present invention;

[0061] Figure 3 This is a density change and compression curve diagram of the silicon dioxide composite thermal insulation aerogel prepared in Example 1 of the present invention;

[0062] Figure 4 This is the infrared spectrum of the silicon dioxide composite thermal insulation aerogel prepared in Example 1 of the present invention;

[0063] Figure 5 This is a SEM image of the silica composite thermal insulation aerogel prepared in Example 1 of the present invention;

[0064] Figure 6 This is a graph showing the thermal weight loss change of the silicon dioxide composite thermal insulation aerogel prepared in Example 1 of the present invention;

[0065] Figure 7 Schematic diagram of the oil absorption application and water contact angle of the silica composite thermal insulation aerogel prepared in Example 1 of the present invention;

[0066] Figure 8 This is a density change and compression curve diagram of the silicon dioxide composite thermal insulation aerogel prepared in Example 2 of the present invention;

[0067] Fig. 9 Schematic diagram of the oil-water separation performance test and recycling performance of the silica composite thermal insulation aerogel prepared in Example 2 of the present invention;

[0068] Fig.10 This is a SEM image of the silicon dioxide composite thermal insulation aerogel prepared in Example 3 of the present invention;

[0069] Fig.11 This is an EDS analysis chart of the silica composite thermal insulation aerogel prepared in Example 3 of the present invention;

[0070] Fig.12 This is a comparison chart of the FT-IR spectra of the silica composite thermal insulation aerogel prepared in Example 3 of the present invention;

[0071] Fig.13 TG and DTG curves of the silica composite thermal insulation aerogel prepared in Example 3 of the present invention;

[0072] Fig.14 This is a comparison chart of the hydrophobic angle and dye adsorption rate of the silica composite thermal insulation aerogel prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0073] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings.

[0074] A silicon dioxide composite thermal insulation aerogel, the raw materials for making the aerogel include, by weight:

[0075] 0.36-0.98 parts of chitosan, 0.746-0.776 parts of acetic acid, 0.885 parts of methyltrimethoxysilane, 0.295 parts of tetraethoxysilane, 3.267 parts of ethanol, 0.916 parts of o-phthalaldehyde, 0.5 parts of silicic acid, and 29.256-29.689 parts of water;

[0076] Furthermore, the raw materials for making the aerogel further include, by weight: 0.4 parts of sodium lauroyl glutamate and 0.5-3 parts of phytic acid;

[0077] Furthermore, the raw materials for making the aerogel further include, by weight: 3-5 parts of aqueous ammonia, 5-20 parts of n-hexane, and 1-3 parts of trimethylchlorosilane.

[0078] Example 1

[0079] An embodiment of the silica composite thermal insulation aerogel of the present invention comprises the following steps:

[0080] 11. Mix 0.7 parts of chitosan and 0.76 parts of acetic acid, and stir to dissolve to obtain a chitosan solution;

[0081] The volume percentage concentration of the acetic acid solution was set to 3% v / v, the stirring time was 5 h, the stirring temperature was 50° C., and after stirring and dissolving, four chitosan solutions with different weight percentage concentrations were obtained, specifically: 1.5wt% chitosan solution, 2wt% chitosan solution, 3wt% chitosan solution, and 4wt% chitosan solution;

[0082] 12. Add 0.885 parts of methyltrimethoxysilane, 0.295 parts of tetraethoxysilane and 3.267 parts of ethanol to 10 parts of water, stir and mix, and let stand to obtain silica sol;

[0083] The stirring time is 1 hour, the stirring temperature is 23°C, and the pH value is adjusted during stirring to a pH value of 2-3, and the standing time is 24 hours;

[0084] 13. Mix 0.916 parts of o-phthalaldehyde powder with 5.234 parts of water, and stir to dissolve to obtain an o-phthalaldehyde solution;

[0085] Among them, the stirring time is 10h and the stirring temperature is 65℃;

[0086] 14. Mix 25 parts of chitosan solution with 6 parts of o-phthalaldehyde solution, add 0.5 parts of silicic acid and 5 parts of silica sol for secondary stirring after the first stirring, and then transfer the stirred solution to a polypropylene mold and freeze it to prepare a cryogel;

[0087] Wherein, the chitosan solution has a weight percentage concentration of any one of 1.5wt%, 2wt%, 3wt%, and 4wt%;

[0088] Among them, the first stirring time is 3 minutes, the second stirring time is 5 minutes, the freezing temperature is -48°C, and the freezing time is 24 hours;

[0089] 15. Transfer the frozen gel to a freeze dryer for vacuum freeze drying to obtain a silica composite thermal insulation aerogel;

[0090] Among them, the drying temperature is -48°C and the drying time is 48h.

[0091] At the same time, according to different chitosan concentrations (x) and composition ratios (SA:CS = a:b), the silica composite thermal insulation aerogel is named xOPAab (for example, when the chitosan concentration is 3wt% and the ratio of silicic acid to chitosan solution is 5:1, it is named 3OPA51.

[0092] Example 2

[0093] An embodiment of the silica composite thermal insulation aerogel of the present invention comprises the following steps:

[0094] 2.1. Mix 0.7 parts of chitosan with 0.76 parts of acetic acid, and stir to dissolve to obtain a chitosan solution;

[0095] The volume percentage concentration of the acetic acid solution was set to 3% v / v, the stirring time was 5 h, the stirring temperature was 50° C., and after stirring and dissolving, four chitosan solutions with different weight percentage concentrations were obtained, specifically: 1.5wt% chitosan solution, 2wt% chitosan solution, 3wt% chitosan solution, and 4wt% chitosan solution;

[0096] The stirring time is 1 hour, the stirring temperature is 23°C, and the pH value is adjusted during stirring to a pH value of 2-3, and the standing time is 24 hours;

[0097] 22. Mix 0.916 parts of o-phthalaldehyde powder with 5.234 parts of water, and stir to dissolve to obtain an o-phthalaldehyde solution;

[0098] Among them, the stirring time is 10h and the stirring temperature is 65℃;

[0099] 23. Mix 25 parts of chitosan solution with 6 parts of o-phthalaldehyde solution, add 0.5 parts of silicic acid, 0.4 parts of sodium lauroyl glutamate, and 0.5-3 parts of phytic acid after the first stirring, stir for the second time, and then transfer the stirred solution to a polypropylene mold and freeze it to prepare a frozen gel;

[0100] Wherein, the chitosan solution has a weight percentage concentration of any one of 1.5wt%, 2wt%, 3wt%, and 4wt%;

[0101] Among them, the first stirring time is 3 minutes, the second stirring time is 5 minutes, the freezing temperature is -48°C, and the freezing time is 24 hours;

[0102] Among them, phytic acid can be replaced by melamine or aluminum hydroxide (chemical formula is Al(OH)3);

[0103] 24. Transfer the frozen gel to a freeze dryer for vacuum freeze drying to obtain a silica composite thermal insulation aerogel;

[0104] Among them, the drying temperature is -48℃ and the drying time is 48h;

[0105] At the same time, according to the different chitosan concentrations and the different flame retardant components added, the composite aerogel with a chitosan concentration of 3wt% prepared by the above steps was named F351, and the composite aerogel with a chitosan concentration of 3wt% and phytic acid as the flame retardant component prepared by the air template method was named F351P.

[0106] Example 3

[0107] An embodiment of the silica composite thermal insulation aerogel of the present invention comprises the following steps:

[0108] 3.1. Add 0.885 parts of methyltrimethoxysilane, 0.295 parts of tetraethoxysilane and 3.267 parts of ethanol to 0.422 parts of water, stir and mix, let stand to obtain silica sol, and age, ball-mill and dry the sol to obtain aerogel powder;

[0109] The stirring time was 1 h, the stirring temperature was 23°C, the pH value was adjusted to 3 during stirring, and the standing time was 24 h;

[0110] The aging process is as follows: the silica sol is treated in an autoclave at a temperature of 100°C for 20 h;

[0111] The ball milling process is as follows: the aged silica sol is added with 3.267 parts of ethanol and 3-5 parts of ammonia water for ball milling, and after a period of time, 2-20 parts of n-hexane and 1-3 parts of trimethylsilyl chloride are added for further ball milling to obtain a dispersion;

[0112] Among them, one period is half of the entire ball milling treatment time;

[0113] The drying process is specifically as follows: drying the dispersion in a vacuum drying oven to obtain silica aerogel powder;

[0114] The dispersion was dried in a vacuum drying oven at 55°C, 90°C, 115°C and 0.08-0.09MPa for 4 hours to obtain silica aerogel powder.

[0115] 3.2. Add 0.58 parts of chitosan to 15 parts of isopropanol, then slowly drop glycidyl trimethylammonium chloride, stir, heat, precipitate, soak, rinse and dry to obtain quaternized chitosan;

[0116] The stirring process is as follows: the stirring time is 1 hour, the stirring temperature is 40° C., and in the process of maintaining the stirring, glycidyl trimethyl ammonium chloride is added dropwise to the mixture of chitosan powder and isopropanol;

[0117] The specific heating process is as follows: a mixture of chitosan powder, isopropanol and glycidyl trimethylammonium chloride is heated to 80°C in a flask and maintained for 3 hours to obtain a mixed solution.

[0118] The precipitation, soaking and rinsing process is specifically as follows: the mixed solution is transferred into acetone to form a precipitate, the precipitate is removed and then repeatedly soaked and rinsed with ethanol to obtain an unreacted white insoluble substance;

[0119] The specific drying process is as follows: after drying the white insoluble matter in a forced air drying oven for 36 hours, quaternized chitosan can be obtained;

[0120] 3.3, 3.3-5.5 parts of quaternized chitosan and 1.1 parts of chitosan are mixed and dissolved in 0.76 parts of acetic acid, and stirring is continued to obtain a quaternized chitosan solution;

[0121] The acetic acid was set to 100 ml of 4 wt% glacial acetic acid solution, the stirring time was 8 h, and the stirring temperature was 50°C;

[0122] 3.4. Add 0.1-0.5 parts of silica aerogel powder into the quaternary ammonium chitosan solution, mix and stir, transfer to a polypropylene mold for freezing, and after freezing, transfer to a freeze dryer for drying to obtain a silica composite thermal insulation aerogel.

[0123] Verification experiment

[0124] 1. Silicon dioxide composite thermal insulation aerogel prepared in Example 1

[0125] The physical properties, functional group changes, micromorphology, thermal weight loss behavior and hydrophobicity of the silica composite thermal insulation aerogel prepared in Example 1 were tested. The experimental results are as follows: Figure 2-7 As shown;

[0126] 1. About physical properties

[0127] according to Figure 2 The left picture of the silica composite thermal insulation aerogel shows that the silica composite thermal insulation aerogel has a perfect cylindrical structure. Compared with pure chitosan aerogel, the silica composite thermal insulation aerogel is light yellow.

[0128] according to Figure 2 The shrinkage rate of the silica composite thermal insulation aerogel shown in the right figure shows that by using o-phthalaldehyde as a cross-linking agent, the shrinkage rate of the silica composite thermal insulation aerogel produced is small, and no matter how the percentage concentration of the chitosan solution used changes, specifically any one of 1.5wt%, 2wt%, 3wt%, and 4wt%, the shrinkage rate of the silica composite thermal insulation aerogel is less than 8%;

[0129] Therefore, it can be concluded that the two aldehyde groups of o-phthalaldehyde are in a rigid state after reacting with chitosan, playing a supporting role in the chitosan and silica skeleton, and the prepared silica composite thermal insulation aerogel has a high skeleton strength;

[0130] At the same time, since the water in the silica composite thermal insulation aerogel forms larger ice crystals during the freezing process, these ice crystals sublimate and disappear during vacuum freeze drying, and the pore structure formed by these ice crystals is retained, thereby increasing the number of pores in the silica composite thermal insulation aerogel. At the same time, the sublimation of ice crystals has little damage to the skeleton, which can better maintain the original size of the silica composite thermal insulation aerogel and reduce volume shrinkage.

[0131] in, Figure 3The density table of silica composite thermal insulation aerogel shown in the middle right figure shows that the density of the prepared silica composite thermal insulation aerogel is as low as 0.47g / cm3. This is because during the freeze-drying process, the water in the system forms ice crystals, which gives the aerogel system a certain large pore structure. At the same time, the rich porous structure formed by the chitosan aerogel is retained, which is the characteristic of the aerogel structure itself. Furthermore, by using o-phthalaldehyde as a cross-linking agent, the two aldehyde groups of o-phthalaldehyde lose the ability to rotate after reacting with the amino group of chitosan, giving the chitosan gel better rigidity, that is, giving the silica composite thermal insulation aerogel a stronger ability to resist shrinkage. As the concentration of chitosan used increases, the density of the produced silica composite thermal insulation aerogel also increases, but the overall density remains below 0.07g / cm3.

[0132] Figure 3 The compression curve of the silica composite thermal insulation aerogel shown in the middle left figure. Combined with the compression curve, it can be seen that the compression modulus of pure chitosan aerogel is significantly lower than that of the silica composite thermal insulation aerogel. In addition, with the increase of chitosan concentration, the compression strength increases significantly. The compression strength of 4OPA51 reaches 0.35MPa. This is because the increase in chitosan concentration increases the proportion of amino groups in the system, further increasing the reaction probability of chitosan and o-phthalaldehyde, forming more dense cross-linking bonds, which makes the compression strength and compression modulus of the composite aerogel significantly improved.

[0133] 2. About functional group changes and microscopic morphology

[0134] Depend on Figure 4 The infrared spectrum of the silica composite thermal insulation aerogel shown in the figure, where the black line is the infrared spectrum of the o-phthalaldehyde used, and the most obvious one is at 1700cm -1 The left and right are the stretching vibration peaks of the aldehyde group C=O, which have high intensity and are obvious in the infrared spectrum;

[0135] 2850cm -1 The stretching vibration peaks of CH in the aldehyde group are on the left and right, with weak intensity at 975-780cm -1 The range is the out-of-plane bending vibration peak of CH in the aldehyde group;

[0136] 719-800cm -1 In between are the out-of-plane bending vibration peaks of CH on the ortho-disubstituted benzene ring, and the peak intensity is extremely strong;

[0137] And from Figure 4As shown in the red box, when o-phthalaldehyde is used as a crosslinker in the composite aerogel system, it can be observed that the CH out-of-plane bending vibration peak of the o-disubstituted benzene ring is still retained in the composite aerogel system, and compared with the infrared spectrum of chitosan, the peak at 1700cm -1 There is a more prominent aldehyde peak at the end, which indicates that in the relatively fast gelation process of the whole system, a part of the o-phthalaldehyde quickly connects the chitosan and silica system to form a macroscopic solid gel structure, and a part of the o-phthalaldehyde only participates in the reaction at one end, leaving a very small amount of aldehyde group.

[0138] Among them, Figure 5 As shown in Figure a, the silica composite thermal insulation aerogel obtained by vacuum freeze drying has a very large porous structure. This is because the water in the gel will form ice crystals during the freezing process. The ice crystals squeeze the gel skeleton during the formation process. At the same time, the ice crystals are directly removed during vacuum freeze drying, so that a porous structure with many ice crystals is formed in the obtained silica composite thermal insulation aerogel.

[0139] Depend on Figure 5 As shown in Figure b, it is a structure obtained by magnifying the bridge of multiple pore structures of the silica composite thermal insulation aerogel. It can be observed that there are a large number of silica granular structures in the skeleton structure of the silica composite thermal insulation aerogel. The rigid structure formed by the silica particles themselves can give the chitosan skeleton a certain support and reduce the possible shrinkage behavior of the silica composite thermal insulation aerogel. On the other hand, the presence of silica particles can directly give the silica composite thermal insulation aerogel a certain hydrophobicity. The porous structure formed by it can provide more contact sites in the oil-water separation process, which can further enhance the application potential of the silica composite thermal insulation aerogel in the field of oil-water separation, that is, the silica composite thermal insulation aerogel has a better separation effect in oil-water separation.

[0140] Depend on Figure 5 As shown in Figure c, it is the main network structure formed by the silica composite thermal insulation aerogel. It can be seen that some silica particles are attached to the network, which can improve the mechanical strength of the silica composite thermal insulation aerogel. When the silica composite thermal insulation aerogel is subjected to external force, it can more effectively resist deformation and fracture;

[0141] 3. About thermal weight loss behavior and hydrophobic properties

[0142] from Figure 6 It can be seen that the weight loss behavior of silica composite thermal insulation aerogel during thermal weight loss is mainly divided into three parts, specifically:

[0143] The weight loss of the first part occurs at 50-100°C. This part is the weight change caused by the evaporation of the bound water of chitosan in the system. Since the drying method used for the silica composite thermal insulation aerogel here is freeze-drying, its water content is extremely low compared with the composite aerogel obtained by supercritical drying in the second part. The weight loss of this part is less than 3%, which can be basically ignored.

[0144] The weight loss behavior of the second part mainly occurred between 260-420℃. At 315℃, the thermal weight loss rate reached the maximum. The weight loss of this part was mainly due to the breakage of chitosan molecular chains in the silica composite thermal insulation aerogel. Compared with the thermal weight loss process of the composite aerogel obtained by the non-crosslinking method, the temperature of the chitosan molecular chain breakage was significantly delayed, which was about 70℃ later than the thermal decomposition process of conventional chitosan.

[0145] The third part of the weight loss process occurred between 470-670℃, and the thermal weight loss rate of the composite aerogel reached its peak at 531℃. This part of the weight loss occurred because the addition of o-phthalaldehyde improved the overall stability of the silica composite thermal insulation aerogel, and the cross-linked structure between chitosan and silica components was destroyed at this time, accompanied by the complete decomposition of the chitosan molecular chain and the breakage of the alkyl group in the silica component.

[0146] Therefore, it can be concluded that the introduction of o-phthalaldehyde significantly improves the thermal stability of silica composite thermal insulation aerogel, allowing it to maintain the characteristics of low thermal conductivity and high porosity in a high temperature environment, thereby expanding its operating temperature range, enhancing energy-saving effects, and having better thermal insulation performance, and having a wider application prospect in the field of thermal insulation;

[0147] In this Example 1, when selecting the components of the silicon source, methyltrimethoxysilane and tetraethoxysilane were selected and mixed in a ratio of 3:1. After hydrolysis, silica sol was obtained. Methyltrimethoxysilane was the main component of silica sol. Since it contained a certain number of methyl structures, it was finally retained in the formation of the composite aerogel structure.

[0148] And by Figure 7 As can be seen from the middle right figure, the obtained composite aerogel 1.5OPA51 has the highest hydrophobic angle, reaching 134.2°. With the increase of chitosan concentration, the water contact angle of the composite aerogel decreases, but the overall decrease is small. Even the composite aerogel 4OPA51 reaches 130.5°, which means that the silica composite thermal insulation aerogel has a certain degree of hydrophobicity without post-treatment, which is conducive to use.

[0149] 2. Silicon dioxide composite thermal insulation aerogel prepared in Example 2

[0150] The physical properties, thermal weight loss behavior, hydrophobicity and combustion performance of the silica composite thermal insulation aerogel prepared in Example 2 were tested. The experimental results are as follows: Figure 5 (d) Figure 7-9 As shown:

[0151] 1. About physical properties

[0152] As attached Figure 5 As shown in Figure d, under the same magnification as Figure a, the entire page of Figure d presents a denser and more complex pore structure. This is because a large number of bubbles introduced in the experiment, combined with the cross-linked gel of o-phthalaldehyde and rapid freezing molding, allow a large number of bubbles to be retained in the gel. After freeze-drying, such a large number of irregular pore structures are formed, and the separation effect of the silica composite thermal insulation aerogel in oil-water separation is further improved.

[0153] The silica composite thermal insulation aerogel prepared by using sodium lauroyl glutamate to form an air template can be observed through SEM micromorphology, which shows a more complex and larger number of pore structures. This is also reflected in the density and compression curve. Specifically:

[0154] like Figure 8 As shown in the figure, the silica composite thermal insulation aerogel obtained in Example 2 shows similar curve changes during the compression process, and the compression strength of different composite aerogels shows a trend of change in a certain proportional law, and the compression strength is reduced compared with the original composite aerogel without foaming. Comprehensively considering the various changes that occurred in the study, the main reason is that when sodium lauroyl glutamate is used as a foaming agent, a large amount of foaming is retained when it is introduced into the composite aerogel, and a pore structure is finally formed. The increase in the pore structure makes the skeleton connection of the prepared silica composite thermal insulation aerogel finer, which makes the silica composite thermal insulation aerogel more easily deformed as a whole, and the compression strength is reduced. Low, and in addition, the introduction of sodium lauroyl glutamate reduces the damage of ice crystals to the uniformity of pore structure, and the increase of chitosan concentration has a negligible effect on the formation of ice crystals. The presence of sodium lauroyl glutamate as an air template is equivalent to actively separating the area of ​​​​ice crystals, which reduces the probability of forming large-sized ice crystals in the cryogel. With the increase of chitosan concentration in the composite aerogel, the compressive strength and modulus of the composite aerogel increase accordingly, that is, the volume density of the silica composite thermal insulation aerogel after foaming decreases by about 14%, which further indicates that the introduction of sodium lauroyl glutamate as an air template increases the porosity of the aerogel;

[0155] like Fig. 9As shown in the middle left figure, with the increase of chitosan concentration in the silica composite thermal insulation aerogel, the oil absorption value shows a decreasing trend. 1.5OPA51 has the highest oil absorption value in the whole system, reaching 15.65g / g. Specifically:

[0156] On the one hand, because the content of the methyltrimethoxysilane component that provides hydrophobicity in the entire composite aerogel system is the same, the low chitosan concentration shows better hydrophobicity and oil absorption value;

[0157] On the other hand, the network structure formed by increasing chitosan concentration is more complex, and the pore structure increases accordingly, but the macroporous structure formed by vacuum freeze drying will reduce the porosity of the composite aerogel;

[0158] Therefore, combining the above two aspects, it can be seen that in the oil absorption experiment, 1.5OPA51 with a lower chitosan concentration showed a better oil absorption value. This result is because sodium lauroyl glutamate as an air template requires a certain system viscosity to better retain bubbles in the early stage of gelation. Therefore, when the chitosan concentration is low, the prepared silica composite thermal insulation aerogel does not perform well in oil absorption.

[0159] Only F351 and F451 were tested and analyzed here. The oil absorption values ​​of F351 and F451 reached 16.35 g / g and 18.26 g / g respectively, which were better than the original composite aerogel.

[0160] This is because sodium lauroyl glutamate acts as an air template and introduces a large number of bubbles during the gelation process, which forms a large number of pore structures during the freeze-drying process, which also increases the specific surface area of ​​the composite aerogel after foaming, thereby showing better performance in the oil-water separation direction than the original composite aerogel.

[0161] At the same time, three composite aerogels with excellent oil absorption capacity were tested for recycling, such as Fig. 9 As shown in the middle right figure, after 20 cycles of testing, the oil absorption value of the composite aerogel can still reach 90% of the initial oil absorption value, that is, the three composite aerogels all perform well in recycling use, and the silica composite thermal insulation aerogel produced with sodium lauroyl glutamate as an air template performs well in oil absorption.

[0162] 2. About thermal weight loss behavior and hydrophobic properties

[0163] like Figure 7 As shown in the middle left figure, n-hexane is selected as the oil and mixed with water in a ratio of 1:1, and then the n-hexane is dyed with Sudan III to obtain Figure 7The solution on the left side of the figure shows that the silica composite thermal insulation aerogel prepared in Example 2 is placed in the solution. It can be observed that Sudan tri-dyed n-hexane is quickly absorbed and removed from the solution. The silica composite thermal insulation aerogel that has completely absorbed n-hexane finally floats on the water surface. Figure 7 The contact angle comparison in the right figure shows that the chitosan aerogel can be given a certain hydrophobic property by treating it with trimethylchlorosilane vapor. Figure 2 It can be seen that the water contact angle of the silica composite thermal insulation aerogel is significantly higher than that of the hydrophobized chitosan aerogel. The introduction of methyltrimethoxysilane as a silicon source can give the composite aerogel good hydrophobicity while reducing the post-processing time and shortening the entire process.

[0164] 3. About combustion performance

[0165] Since sodium lauroyl glutamate is used as an air template to produce silica composite thermal insulation aerogel, special functional materials can be added to the composite aerogel to be prepared through relatively simple operations, and the composite aerogel to be prepared uses chitosan as the main material. The formed composite aerogel is very easy to burn in a normal environment. Since Al(OH)3 is a solid flame retardant component commonly used in the Al(OH)3 polymer flame retardant system, it has a certain solubility in water and can be added to the composite aerogel component in the form of a suspension. Melamine is a liquid component, which can be added to the composite aerogel in a simpler way. In the present embodiment 2, the above three commonly used flame retardants are selected and introduced into the gel system, and the combustion performance of the finally prepared silica composite thermal insulation aerogel is measured to obtain Table 1 (the influence of different Al (OH) 3 contents on the combustion performance of silica composite thermal insulation aerogel), Table 2 (the influence of different melamine contents on the combustion performance of silica composite thermal insulation aerogel), Table 3 (the influence of different phytic acid contents on the combustion performance of silica composite thermal insulation aerogel), the specific tables are as follows:

[0166] Table 1

[0167] <![CDATA[Content of Al(OH)3 (g)]]> LOI(%) Vertical burning level 0(pure F1.551) 18 V-2 0.5 23 V-1 1 25.5 V-0 1.5 26 V-0 3 27 V-0

[0168] Table 2

[0169] Melamine content (g) LOI(%) Vertical burning level 0(pure F1.551) 18 V-2 0.5 22.5 V-2 1 26.5 V-0 1.5 27 V-0 3 28 V-0

[0170] Table 3

[0171] Phytic acid content (g) LOI(%) Vertical burning level 0(pure F1.551) 18 V-2 0.5 26 V-2 1 26.5 V-0 1.5 27 V-0 3 28 V-0

[0172] As can be seen from Table 1 above, the addition of Al(OH)3 significantly increases the oxygen index of the silica composite thermal insulation aerogel, and the silica composite thermal insulation aerogel changes from violent combustion to natural extinguishing. However, when the amount of Al(OH)3 added reaches 1g, the effect on the oxygen index (LOI) of the silica composite thermal insulation aerogel is weakened. When the amount of addition is increased to 3g, the oxygen index of the silica composite thermal insulation aerogel is only increased from 25.5% to 27%. In addition, in the process of forming the composite aerogel by the non-crosslinking method (i.e., without using o-phthalaldehyde as a crosslinking system), an attempt was made to introduce Al(OH)3 as a flame retardant component (belonging to the prior art, and the specific experimental process is not given in this application). It was found that the presence of Al(OH)3 interfered with the pH change of the entire system, thereby interfering with the gel process. With the increase of the Al(OH)3 component, not only the oxygen index increases less, but also the surface of the composite aerogel is full of powdered Al(OH)3, which is prone to powdering, which has a negative impact on other applications of the composite aerogel, so it is abandoned.

[0173] It can be seen from Table 2 that when melamine is selected as the flame retardant component, the flame retardant effect is relatively better than that of Al(OH)3. When the amount of melamine added is small, its flame retardant effect is lower than that of Al(OH)3. As the amount of melamine added increases, its flame retardant effect gradually exceeds that of Al(OH)3. When the amount of melamine added reaches 3g, the oxygen index of the composite aerogel reaches 28%, and because melamine itself is a liquid component, no powdering occurs in the composite aerogel obtained after drying.

[0174] As shown in Table 3, when phytic acid is selected as a flame retardant, phytic acid rapidly generates electrostatic adsorption with unreacted amino groups after addition to generate a NP compound system with flame retardancy. However, when the phytic acid component is 0.5 g, the oxygen index of the system reaches 26%. However, after electrostatic adsorption, phytic acid easily generates a precipitate that is insoluble in the system. When the content of phytic acid continues to increase, the amount of precipitation increases accordingly and cannot be dispersed in the gel.

[0175] It can be seen from Tables 1-3 that the addition of the three flame retardant ingredients, whether Al(OH)3 of the powder component, melamine of the liquid component, or phytic acid having a certain reactivity with the system, improves the flame retardancy of the silica composite thermal insulation aerogel without damaging the overall gel process, thus providing a simpler channel for expanding the function of the silica composite thermal insulation aerogel.

[0176] 3. Silicon dioxide composite thermal insulation aerogel prepared in Example 3

[0177] The microscopic morphology, functional group structure and heat resistance, hydrophobic angle and dye adsorption performance of the silica composite thermal insulation aerogel prepared in Example 3 were tested. The experimental results are as follows: Figure 10-14 As shown:

[0178] 1. About microscopic morphology

[0179] like Fig.10 As shown in Figure a, it can be seen that the silica composite thermal insulation aerogel presents a layered distribution structure in the longitudinal direction. Its entire cross section is composed of pieces of chitosan sheet structures. There are also many tree-like structures between the layered structures. This is because, during the freeze-drying process, the formation of ice crystals is oriented. It is only necessary to control the temperature of the entire gel to slowly decrease from bottom to top during freezing, that is, to control the water content in the gel to tend to form layers of ice crystal structures. The presence of multi-layer sheet structures in the aerogel is conducive to increasing the surface area of ​​the entire gel. In the subsequent dye adsorption process, it is conducive to increasing the contact area between the quaternary ammonium structure in the gel and the dye, thereby improving the adsorption capacity of the composite aerogel for anionic dyes.

[0180] At the same time, it can be seen from Figure c that the transverse structure of the silica composite thermal insulation aerogel is a relatively complete sheet structure full of pores. The appearance of pores on the sheet structure is related to the structure of the silica composite thermal insulation aerogel. Specifically, it is because the silica aerogel powder has been hydrophobically treated and cannot be naturally mixed with the chitosan solution. The process of mixing the aerogel powder into the chitosan solution by high-speed stirring will have a great impact on the viscosity of the system. In the gel process, water forms ice crystals unevenly and discontinuously in the longitudinal direction. Part of the gel cannot react in time due to the influence of viscosity. Therefore, after the ice crystals are removed in freeze drying, an uneven pore structure is left. The presence of pores on the surface of the aerogel can promote the flow of dye wastewater in the aerogel, making it easier to fill the entire gel and improve the overall utilization rate of the gel adsorbed dye;

[0181] Figure d is an enlarged version of Figure c. It can be seen from Figure d that a large number of silica aerogel particles are filled on the surface of the sheet gel, and the pore structure of the silica composite thermal insulation aerogel is not destroyed, and the whole is fixed by a large amount of chitosan gel. Therefore, the presence of silica aerogel can support the chitosan skeleton. At the same time, due to the presence of hydrophobic silica aerogel, the chitosan in the aerogel monolithic structure forms a more complex and elongated skeleton structure.

[0182] in, Fig.11 This is the EDS analysis diagram of the silica composite thermal insulation aerogel. Specifically, Fig.11 for Fig.10 The EDS element analysis diagram of Figure d in the figure, from Fig.11It can be seen that the N element only exists in the chitosan component. By observing the distribution of the N element, it can be clearly found that its position is completely consistent with the chitosan skeleton. The Si element mainly exists in the silica aerogel and exists in large quantities in the observation area. The C element mainly exists in the chitosan component, but the presence of the hydrophobic alkyl structure of the silica aerogel makes the C element have a larger distribution area than the N element.

[0183] 2. About functional group structure and heat resistance

[0184] like Fig.12 As shown, the FT-IR spectrum curve of the silica composite thermal insulation aerogel prepared in Example 3 is relatively simple, in which it can be clearly observed that the -1 The strong Si-O-Si antisymmetric stretching vibration peak at 810 cm -1 and 466cm -1 The absorption peak of Si-O bond is also very obvious at 1478cm. However, due to the hydrophobic treatment of the silica composite thermal insulation aerogel, the hydrophobic group -CH3 and the hydrophilic group -Si-OH are weak, with only a small absorption peak. By comparing the infrared spectra of chitosan and quaternized chitosan, it can be clearly seen that the absorption peak at 1478cm -1 The vibration absorption peak of the methyl group of the quaternary ammonium salt introduced into chitosan was observed at 2025 cm -1 、1478cm -1 ,1111cm -1 、810cm -1 、474cm -1 They all show the same infrared absorption peak;

[0185] And if Fig.13 As shown, it can be seen that the thermal weight loss behavior of silica composite thermal insulation aerogel at different proportions is exactly the same. Obviously, the thermal weight loss process can be divided into three stages, specifically:

[0186] Between 30℃ and 250℃, thermal weight loss behavior continues to occur, and the rate of thermal weight loss is relatively small. The reason for this period of weight loss is that the quaternized silica composite thermal insulation aerogel has a certain hygroscopicity. The absorbed water in the silica composite thermal insulation aerogel and the gasification of the bound water in the chitosan structure lead to the continuous occurrence of weight loss behavior.

[0187] Between 250℃ and 300℃, the thermal weight loss rate of the silica composite thermal insulation aerogel is the fastest stage, which is due to the rapid degradation of the chitosan component in the sheet structure of the aerogel and the formation of coke;

[0188] Between 300℃ and 600℃, the weight loss rate of the silica composite thermal insulation aerogel slowed down compared with the previous stage. This stage mainly corresponds to the complete degradation of the chitosan component and carbon slag, and finally only silica aerogel remains in the system.

[0189] Among them, the proportion of silica powder in the overall silica composite thermal insulation aerogel can be known according to the proportion of undecomposed components. For example, when the solubility of quaternized chitosan is 3wt%, the added 0.1g and 0.3g silica powder account for 26% and 34% of the composite aerogel respectively, which indicates that the increase of silica powder is well dispersed in the chitosan sol, but as the mass of the powder further increases to 0.5g, the proportion in the overall aerogel reaches 35%, which indicates that it is not well dispersed in the gel.

[0190] 3. About hydrophobic angle and dye adsorption performance

[0191] like Fig.14 As shown in the figure, it is a graph showing the hydrophobic angle change and dye adsorption test experimental results of the silica composite thermal insulation aerogel. It can be seen that in the preparation process of the silica aerogel powder, due to the hydrophobic treatment and the introduction of hydrophobic methyl groups, a composite aerogel with an open silica pore structure and a complex chitosan network skeleton was successfully prepared by utilizing the hydrophobic phenomenon. Due to the close combination of the two phases and the fact that the silica powder still occupies a small part in the system, the silica composite thermal insulation aerogel can still show good hydrophilicity.

[0192] like Fig.14 As shown in the left figure, the water contact angle of the silica composite thermal insulation aerogel is below 25°, and increases slightly with the increase of silica aerogel powder content;

[0193] like Fig.14As shown in the right figure, further, the adsorption performance of chitosan powder, chitosan aerogel and the silica composite thermal insulation aerogel for dyes was tested in the same concentration and volume of dye solution. It can be seen that the adsorption effect of chitosan powder on dye CR is 21% higher than that of the other two dyes. The adsorption performance of chitosan aerogel is better than that of chitosan particles. Chitosan aerogel has a larger contact area and can rely on the rough surface to intercept some dye particles, but because it lacks the corresponding reaction group, it does not show very excellent characteristics in the adsorption of anionic dyes. The adsorption ratio of the three dyes is basically maintained at about 25%, while the silica composite thermal insulation aerogel shows excellent adsorption performance. The presence of its layered lamellar structure gives it sufficient contact area. The presence of silica particles can not only maintain the structure of the aerogel, but also increase the roughness of the lamellar surface in the aerogel, thereby improving the retention capacity of the composite aerogel for dye particles.

[0194] Experimental Summary

[0195] The present application prepares a silica composite thermal insulation aerogel by using o-phthalaldehyde as a cross-linking agent, analyzes the influence of the change of chitosan concentration and the reaction of o-phthalaldehyde on the prepared silica composite thermal insulation aerogel during the gelation process, and on this basis, uses sodium lauroyl glutamate as an air template to prepare a silica composite thermal insulation aerogel with a larger number of pore structures and a higher oil absorption value, and further draws the following conclusions through experimental analysis:

[0196] 1. The addition of o-phthalaldehyde reduces the shrinkage of the prepared silica composite thermal insulation aerogel, and the maximum shrinkage does not exceed 8%, and the density is also maintained at a low level. With the increase of chitosan concentration, the density of the silica composite thermal insulation aerogel increases, and the density of the composite aerogel is maintained between 0.05-0.07g / cm3;

[0197] 2. The thermal gravimetric analysis showed that the thermal gravimetric curve of the silica composite thermal insulation aerogel was divided into three stages compared with the normal two-stage thermal gravimetric curve of chitosan. That is, the introduction of o-phthalaldehyde delayed the decomposition temperature of the chitosan molecular chain by about 50-70°C, thereby improving the high temperature resistance of the silica composite thermal insulation aerogel.

[0198] 3. The microstructure of the silica composite thermal insulation aerogel was observed through SEM images, and it was concluded that the prepared silica composite thermal insulation aerogel was filled with a large number of pore structures, and the silica composite thermal insulation aerogel prepared with sodium lauroyl glutamate as an air template had a smaller pore structure and a larger number of pores. In addition, methyltrimethoxysilane was used as a silane to give the silica composite thermal insulation aerogel good hydrophobicity. With the increase of chitosan concentration, the water contact angle of the silica composite thermal insulation aerogel decreased, but remained above 130° as a whole. At the same time, the oil absorption value of the silica composite thermal insulation aerogel can reach up to 15.65g / g. The foamed silica composite thermal insulation aerogel showed a higher oil absorption value and a number of cyclic applications. The oil absorption value reached more than 18g / g, and after 20 cycles of adsorption and desorption of n-hexane, it still had about 90% of the initial performance.

[0199] 4. In the silica composite thermal insulation aerogel prepared by using sodium lauroyl glutamate as an air template, functional components can be easily added, that is, three flame retardants with different properties and states, namely Al(OH)3, melamine or phytic acid, are selected to be added to the gel system. The obtained silica composite thermal insulation aerogels all show excellent flame retardancy, with the highest oxygen index reaching about 28%. The reactions caused by the addition of the three flame retardants have their own advantages and disadvantages. Among them, melamine performs better with the increase of the added amount. There is no powdering phenomenon after excessive addition of Al(OH)3, and there is no precipitation after excessive addition of phytic acid.

[0200] Furthermore, by using quaternized chitosan and silica composite aerogel powder as raw materials, quaternized composite aerogel, that is, the silica composite thermal insulation aerogel in Example 3, was prepared, and after a series of experiments, the following conclusions were drawn:

[0201] 5. The addition of hydrophobic silica aerogel powder changes the common microstructure of chitosan aerogel, that is, the pore structure of silica particles in the newly prepared silica composite thermal insulation aerogel is retained, and the presence of a large amount of silica particles on the surface of the silica composite thermal insulation aerogel increases the surface roughness of the system structure. In addition, the layer-by-layer freezing design during freezing causes the silica composite thermal insulation aerogel to form a layered sheet structure, which increases the specific surface area of ​​the silica composite thermal insulation aerogel and makes the silica composite thermal insulation aerogel show anisotropy in the compression curve;

[0202] 6. The spectrum of the silica composite thermal insulation aerogel shows excellent similarity with quaternary ammonium chitosan and silica aerogel. During the thermal weight loss process, the thermal weight loss curve stages of the silica composite thermal insulation aerogel and quaternary ammonium chitosan are also very similar;

[0203] 7. Although hydrophobic silica aerogel powder is added to the silica composite thermal insulation aerogel, the two are closely combined and the silica component is not added much (less than 30% in thermal weight loss), so the whole shows good hydrophilicity, and the water contact angle does not exceed 25°. The silica composite thermal insulation aerogel performs far better than chitosan aerogel in the anion dye adsorption experiment, which can be attributed to the improved surface roughness of silica particles, the successful quaternization of silica composite thermal insulation aerogel, and the successful design of layered lamellar structure.

[0204] In summary

[0205] The present application selects chitosan and silica as the main raw materials of composite aerogel, and uses o-phthalaldehyde as a cross-linking agent to prepare a silica composite thermal insulation aerogel with thermal insulation function, high skeleton strength and good adsorption capacity. On this basis, a new silica composite thermal insulation aerogel is prepared using sodium lauroyl glutamate as an air template. Under the premise of not destroying the overall gel process, the porosity of the aerogel is increased, the separation effect in oil-water separation is further improved, and excellent flame retardancy is exhibited. Finally, chitosan is modified by quaternization and then directly composited with hydrophobic silica aerogel powder to obtain an improved silica composite thermal insulation aerogel, which not only has a more complex and elongated skeleton structure, but also increases the overall surface area and surface roughness of the gel, so that its adsorption capacity is further enhanced. Specifically:

[0206] 1. A silica composite thermal insulation aerogel was prepared by a cross-linking method. As the concentration of chitosan increased, the complexity of the chitosan network increased, providing more attachment sites for silica particles, so that the density of the silica composite thermal insulation aerogel increased to a certain extent, and the volume shrinkage decreased. Correspondingly, the particle density of silica increased, and the average pore size decreased. The water contact angle of the silica composite thermal insulation aerogel increased, and the thermal conductivity decreased accordingly, showing a large amount of chitosan network structure and a small amount of silica aerogel particle structure. The two together played a supporting role, so that the skeleton strength of the prepared silica composite thermal insulation aerogel was relatively high.

[0207] At the same time, in terms of thermal weight loss, the chitosan component in the system reached more than 48%, which shows that in the early stage of gelation, the chitosan molecular chain was shrunk and entangled by the anti-solvent ethanol, and wrapped a certain amount of silica solution to form an insoluble gel. The stability of the system was destroyed by the chitosan gel, causing the self-assembly gel behavior of the entire system, so that the silica composite thermal insulation aerogel has extremely excellent porosity, that is, it can still maintain the characteristics of low thermal conductivity and high porosity in a high temperature environment, which can expand its operating temperature range, enhance energy-saving effects, and has excellent hydrophobicity and adsorption properties. The thermal insulation performance is also guaranteed;

[0208] 2. A new silica composite thermal insulation aerogel is prepared by using o-phthalaldehyde as a cross-linking agent and sodium lauroyl glutamate as an air template. A large number of bubbles generated by sodium lauroyl glutamate under mechanical stirring are used to form an air template. Flame retardant components can be directly mixed into the silica composite thermal insulation aerogel to improve the performance without affecting the gel reaction. The prepared silica composite thermal insulation aerogel exhibits excellent anti-shrinkage performance after o-phthalaldehyde cross-linking, and the overall shrinkage rate is maintained below 8%. At the same time, after adding sodium lauroyl glutamate, the prepared silica composite thermal insulation aerogel has an increased number of irregular pores, a reduced density, a decreased compression strength, and improved oil absorption performance. When the flame retardant component is introduced during the foaming process, the silica composite thermal insulation aerogel changes from violent combustion to natural extinguishing. The system exhibits good compatibility, thereby improving the flame retardant ability of the silica composite thermal insulation aerogel without destroying the entire gel system.

[0209] 3. Further, quaternized chitosan and silica aerogel powder are used to prepare quaternized silica composite thermal insulation aerogel in an incompatible system. The silica composite thermal insulation aerogel presents a layered sheet structure as a whole. On the sheet surface, the silica and chitosan components are tightly combined. The silica particles retain the pore structure while giving the silica composite thermal insulation aerogel a certain support, so that the silica composite thermal insulation aerogel has a higher skeleton strength;

[0210] At the same time, the thermal weight loss process of the silica composite thermal insulation aerogel shows that the composite of ammonium chitosan and silica aerogel powder does not affect the high temperature resistance of the finished silica composite thermal insulation aerogel.

[0211] In addition, although a small amount of hydrophobic silica powder changes the structure of the finished silica composite thermal insulation aerogel, it does not significantly affect the water contact angle of the gel. The silica composite thermal insulation aerogel shows better adsorption performance in the dye adsorption test. The adsorption ratio of the three anionic dyes reaches about 95%, and the adsorption capacity is further enhanced.

[0212] The above description is only by way of illustration of certain exemplary embodiments of the present invention. It is undoubted that those skilled in the art can modify the described embodiments in various ways without departing from the spirit and scope of the present invention. Therefore, the above drawings and descriptions are illustrative in nature and should not be construed as limiting the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a silica composite thermal insulation aerogel, characterized in that it comprises the following steps: 1.

1. Mix 0.39-0.98 parts of chitosan and 0.746-0.776 parts of acetic acid, and stir to dissolve to obtain a chitosan solution; The volume percentage concentration of the acetic acid solution was set to 3% v / v, the stirring time was 5 h, the stirring temperature was 50° C., and after stirring and dissolving, four chitosan solutions with different weight percentage concentrations were obtained, specifically: 1.5wt% chitosan solution, 2wt% chitosan solution, 3wt% chitosan solution, and 4wt% chitosan solution; 1.

2. Add 0.885 parts of methyltrimethoxysilane, 0.295 parts of tetraethoxysilane and 3.267 parts of ethanol to 0.422 parts of water, stir and mix, and let stand to obtain silica sol; The stirring time is 1 hour, the stirring temperature is 23°C, and the pH value is adjusted during stirring to a pH value of 2-3, and the standing time is 24 hours; 1.

3. Mix 0.916 parts of o-phthalaldehyde powder with 5.237 parts of water, and stir to dissolve to obtain an o-phthalaldehyde solution; Among them, the stirring time is 10h and the stirring temperature is 65℃; 1.

4. Mix 25 parts of chitosan solution with 6 parts of o-phthalaldehyde solution. After the first stirring, add 0.5 parts of silicic acid and 5 parts of silica sol for a second stirring. Then transfer the stirred solution to a polypropylene mold and freeze it to prepare a cryogel. Wherein, the chitosan solution has a weight percentage concentration of any one of 1.5wt%, 2wt%, 3wt%, and 4wt%; Among them, the first stirring time is 3 minutes, the second stirring time is 5 minutes, the freezing temperature is -48°C, and the freezing time is 24 hours; 1.

5. Transfer the frozen gel to a freeze dryer for vacuum freeze drying to obtain a silica composite thermal insulation aerogel; in, The drying temperature is -48°C and the drying time is 48h.

2. A method for preparing a silicon dioxide composite thermal insulation aerogel, characterized in that: The following steps are involved: 3.

1. Add 0.885 parts of methyltrimethoxysilane, 0.295 parts of tetraethoxysilane and 3.267 parts of ethanol to 0.422 parts of water, stir and mix, let stand to obtain silica sol, and age, ball-mill and dry the sol to obtain aerogel powder; The stirring time is 1 hour, the stirring temperature is 23°C, and the pH value is adjusted during stirring to a pH value of 2-3, and the standing time is 24 hours; 3.

2. Add 0.36-0.98 parts of chitosan to 10-30 parts of isopropanol, then slowly drop glycidyl trimethylammonium chloride, stir, heat, precipitate, soak, rinse and dry to obtain quaternized chitosan; 3.3, 3.3-5.5 parts of quaternized chitosan and 1.1 parts of chitosan are mixed and dissolved in 0.746-0.776 parts of acetic acid, and stirring is continued to obtain a quaternized chitosan solution; The acetic acid was set to 100 ml of 4 wt% glacial acetic acid solution, the stirring time was 8 h, and the stirring temperature was 50°C; 3.

4. Add 0.1-0.5 parts of silica aerogel powder into the quaternary ammonium chitosan solution, mix and stir, transfer to a polypropylene mold for freezing, and after freezing, transfer to a freeze dryer for drying to obtain a silica composite thermal insulation aerogel; The stirring time was 12 h, and ultrasonic treatment was performed for 30 min after the stirring was completed.

3. The method for preparing a silicon dioxide composite thermal insulation aerogel according to claim 2, characterized in that: In step 3.1: The aging process is as follows: silica sol is treated in an autoclave at 100 °C for 20 h; The ball milling process is as follows: the aged silica sol is added with 3.267 parts of ethanol and 3-5 parts of ammonia water for ball milling, and after a period of time, 2-20 parts of n-hexane and 1-3 parts of trimethylsilyl chloride are added for further ball milling to obtain a dispersion; Among them, one period is half of the entire ball milling treatment time; The drying process is specifically as follows: drying the dispersion in a vacuum drying oven to obtain silica aerogel powder; The dispersion was dried in a vacuum drying oven at 55° C., 90° C., 115° C. and 0.08-0.09 MPa for 4 hours to obtain silica aerogel powder.

4. The method for preparing a silicon dioxide composite thermal insulation aerogel according to claim 2, characterized in that: In step 3.2: The stirring process is specifically as follows: the stirring time is 1 hour, the stirring temperature is 40° C., and in the process of maintaining the stirring, glycidyl trimethyl ammonium chloride is added dropwise to the mixture of chitosan powder and isopropanol; The specific heating process is as follows: a mixture of chitosan powder, isopropanol and glycidyl trimethylammonium chloride is heated to 80°C in a flask and maintained for 3 hours to obtain a mixed solution. The precipitation, soaking and rinsing process is specifically as follows: the mixed solution is transferred into acetone to form a precipitate, the precipitate is removed and then repeatedly soaked and rinsed with ethanol to obtain an unreacted white insoluble substance; The drying process is specifically as follows: after the white insoluble matter is dried in a forced air drying oven for 36 hours, the quaternized chitosan can be obtained.

Citation Information

Patent Citations

  • Thermal insulation composite material based on aerogel and preparation method thereof

    CN115594188A